1993
DOI: 10.1093/oxfordjournals.humrep.a137983
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Ultrasonic monitoring during replacement of frozen/thawed embryos in natural and hormone replacement cycles

Abstract: We evaluated the results of cryopreserved/thawed embryo replacement (FER) to determine if the outcome following transfer in a natural cycle in a defined group was different to that from a hormone replacement cycle, and also to assess vaginal ultrasonographic features that assist in predicting the timing of the transfer. At the London Fertility Centre, 149 consecutive FER cycles were studied retrospectively. Women with proven ovulation and regular cycles were included during natural cycles (n = 77). The hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 0 publications
1
40
1
1
Order By: Relevance
“…Multiple reports have suggested that neither implantation rate nor pregnancy rate is affected by estrogen replacement therapy in cryo-thaw cycles [6,8,9]. HRT cycles are those in which exogenous estrogen and progesterone are administered in order to control and optimize the recipient's hormonal and endometrial environment in preparation for the transfer of the cryo-thawed embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple reports have suggested that neither implantation rate nor pregnancy rate is affected by estrogen replacement therapy in cryo-thaw cycles [6,8,9]. HRT cycles are those in which exogenous estrogen and progesterone are administered in order to control and optimize the recipient's hormonal and endometrial environment in preparation for the transfer of the cryo-thawed embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial thickness has been reported to be a positive prognostic factor in cryo-thaw embryo transfers, with higher success rates when endometrial thickness is greater than 8 mm at a time of transfer [8,14]. Other studies suggest that an endometrial thickness of 10 mm or greater at the time of transfer achieves the best results [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…In four studies comparing natural cycles with GnRH agonist-supported artificial cycles, clinical pregnancy and live births did not differ (46,(47)(48)(49). Furthermore, clinical pregnancy was determined not to differ between the artificial cycles and GnRHsupported artificial cycles (44,50,51).…”
Section: Which Methods Is Preferable?mentioning
confidence: 99%
“…In the natural cycle protocol, patients with normal ovulatory cycles were serially monitored during the follicular phase for serum estradiol, luteinizing hormone and progesterone levels, and transvaginal sonography (TVS) was performed to determine the number and size of the leading follicles and endometrial thickness until ovulation occurred. When LH surge was observed in the serum, coupled with signs of ovulation by transvaginal sonography, thawing and transferring of embryos was planned according to their developmental stage at freezing [17]. Patients in the natural cycle protocol did not receive any medication in order to induce ovulation.…”
Section: Freeze-thaw Embryo Transfer Protocolsmentioning
confidence: 99%